Have Five Decades of Development Engineering Research Improved Sanitation in Southern Africa?. (29th January 2020) - Muller, Mike
Abstract: In developed countries, public health engineering has been closely associated with extensions of life expectancy and declines in infant mortality well beyond the contributions of medicine. However, different approaches have had to be taken in poorer countries. This paper uses cases from South and Southern Africa to illustrate the challenges and the responses and to consider whether these reflect a formal 'development engineering' approach. While external agencies have actively promoted a variety of approaches, engineered interventions were most successful where they took account of social, economic and environmental contexts, reflected local preferences and were developed by, or in close coordination with, the operational institutions concerned. © 2020 John Wiley & Sons, Ltd.